Reģionu attīstība Latvijā – izaugsmes faktori, politikas izvēles, attīstības modeļi - Kalniņa-Lukaševica, Zanda (Latvijas Universitāte, 2013)
Reģionu ekonomiskās attīstības teorijas veido pamatu valstu un reģionu izstrādātām un īstenotām attīstības politikām. Lai veidotu efektīvu attīstības politiku, jāspēj novērtēt iepriekšējos gados realizētās politikas sasniegumi, veiksmes un kļūdas. Pētījuma rezultātā izstrādātā matricveida pieeja, kas balstīta aktuālajos reģionālās zinātnes pētījumos un secinājumos, veido instrumentu kopu šāda novērtējuma izstrādei. Pētījuma jautājums ir - kāds (publiskās pārvaldes īstenots) reģionu ekonomiskās attīstības modelis sekmē Latvijas reģionu ekonomisko attīstību? Pētījuma mērķis ir, izpētot reģionu ekonomisko attīstību ietekmējošos faktorus un publisko politiku izvēles, izstrādāt modeli reģionu ekonomiskās attīstības politiku novērtēšanai un plānošanai. Promocijas darbs sastāv no ievada, piecām nodaļām, noslēguma secinājumiem, priekšlikumiem un izmantotās literatūras saraksta. Pētījuma metodoloģija paredzēja pētījuma īstenošanu desmit loģiski secīgos pētījuma īstenošanas posmos. Pētījumā izmantotas monogrāfiskā, sistēmiskās analīzes, satura analīzes, salīdzināšanas, statistiskā analīzes, sekundārā datu un informācijas analīzes, socioloģiskās aptaujas, gadījumu izpētes, metaanalīzes, ekspertu aptaujas anketas metode, Delfi metode un kabineta pētījums. Pētījuma zinātniskā novitāte: (1) Identificēti nozīmīgākie Baltijas valstu reģionu attīstību virzošie un kavējošie makroekonomiskie faktori; (2) Atklāta saikne starp iedzīvotāju mikrolīmeņa izvēlēm un reģiona makroekonomiskās attīstības tendencēm; (3) Izstrādāts reģionu ekonomiskās attīstības Sintezētais modelis; (4) Izmantojot reģionu ekonomiskās attīstības Sintezēto modeli, izstrādāta matricveida pieeja reģionu ekonomiskās attīstības politiku novērtējumam. Pētījuma rezultāti apliecina, ka lai novērtētu īstenotās reģionu ekonomiskās attīstības politikas un identificētu nepieciešamās izmaiņas, kā analītisks rīks pielietojama matricveida pieeja, kas balstīta autora izstrādātajā reģionu ekonomiskās attīstības Sintezētajā modelī.

The policies designed and implemented by states and regions are based on the theories of regional economic development. In regional science theoretical models undergo dynamic development that is changing the approaches of the regional development policy and its main emphasis. The theories of economic development of regions have close links not only with the regional development policy, but also with the related issues of administration, investments, and public participation. To elaborate an effective development policy, achievements, successes and mistakes of policies implemented in previous years should be evaluated. Question of the study – which (public administration implemented) regional economic development model could facilitate economic development of regions of Latvia? The aim of the study is by exploring impact factors of regional economic development and by exploring public policy alternatives to elaborate a model for evaluation and planning of policies of regional economic development. By assessing the diverse development factors defined in the RED theories, the Synthesized Model of RED was developed. In the result of the research a matrix approach was developed forming a set of tools for evaluation and planning of regional economic development. Based on the Synthesized Model, it is possible to identify four types of regional economic development models. It allows to identify the causations of regional development trends and to assess development potentials in the context of implemented policies, as well as to design recommendations for regional economic development policies. As a result of comparative analysis, recommendations were developed for the regional governance model and for the use of effective development tools for the sustainable and competitive development process. The thesis consists of an introduction part, five chapters, final conclusions, proposals and a bibliography. A methodology of the study envisaged elaboration of the study in ten logically sequential stages. For implementation of the study there were used monographic, systematic analysis, content analysis, comparative, statistical analysis, secondary data and information analysis, sociological survey, case studies, meta-analysis, expert survey method, Delphi method and cabinet study. Scientific novelty of the study: (1) The major macroeconomic factors advancing and preventing the development of the regions of the Baltic states has been identified; (2) A link between the micro level choices of population and trends of macroeconomic development has been proved; (3) The Synthesized Model of the regional economic development has been elaborated; (4) Through the Synthesized Model of the regional economic development, a matrix approach for the evaluation and planning of the economic development policies of regions has been developed. The results of the study affirm that in order to evaluate implemented policies of regional economic development and to identify necessary changes the matrix approach based on the Synthesized model of regional economic development is applicable as analytical tool.
Development of regions in Latvia - model of the regional economic development planning and evaluation
Elektroniskā versija nesatur pielikumus
Keywords: Vadībzinātne; Reģionu attīstība (Latvija); Management; Community development (Latvia)